Clic4, a novel protein that sensitizes β-cells to apoptosis - Dhaval Patel; Damien Ythier; Flora Brozzi; Decio L. Eizirik; Bernard Thorens (Elsevier, 2015)
Objectives: Chloride intracellular channel protein 4 (Clic4) is a ubiquitously expressed protein involved in multiple cellular processes including cell-cycle control, cell differentiation, and apoptosis. Here, we investigated the role of Clic4 in pancreatic β-cell apoptosis. Methods: We used βTC-tet cells and islets from β-cell specific Clic4 knockout mice (βClic4KO) and assessed cytokine-induced apoptosis, Bcl2 family protein expression and stability, and identified Clic4-interacting proteins by co-immunoprecipitation and mass spectrometry analysis. Results: We show that cytokines increased Clic4 expression in βTC-tet cells and in mouse islets and siRNA-mediated silencing of Clic4 expression in βTC-tet cells or its genetic inactivation in islets β-cells, reduced cytokine-induced apoptosis. This was associated with increased expression of Bcl-2 and increased expression and phosphorylation of Bad. Measurement of Bcl-2 and Bad half-lives in βTC-tet cells showed that Clic4 silencing increased the stability of these proteins. In primary islets β-cells, absence of Clic4 expression increased Bcl-2 and Bcl-xL expression as well as expression and phosphorylation of Bad. Mass-spectrometry analysis of proteins co-immunoprecipitated with Clic4 from βTC-tet cells showed no association of Clic4 with Bcl-2 family proteins. However, Clic4 co-purified with proteins from the proteasome suggesting a possible role for Clic4 in regulating protein degradation. Conclusions: Collectively, our data show that Clic4 is a cytokine-induced gene that sensitizes β-cells to apoptosis by reducing the steady state levels of Bcl-2, Bad and phosphorylated Bad.